(untitled) (Research, Society and Development, 2022)
Objective: To analyze the effectiveness of tourniquets in prehospital care, looking at their benefits and possible risks. Methods: This is an integrative literature review, consisting of scientific articles on the theme "The effectiveness of tourniquets in the PHC" For this purpose, the Virtual Health Library (VHL) was used as a research source through the databases: SCIELO and PubMed. Results: Studies report that the early application of tourniquets serves to control damage and reduce mortality in traumatic accidents, as the containment of severe hemorrhages is the first step in the chain of survival. The tourniquet has proven and reported efficacy in controlling bleeding and its application can be performed in about 18.9 seconds, however, no tourniquet is free from complications and the user of such a tool at the PHC must understand its potential risks of complications and respect the length of permanence and reassessment limits. Final Considerations: The use of tourniquets in a civil prehospital environment, despite being much debated, can save lives and prevent damage. The tool allows a quick and effective control of severe hemorrhages, which can be the difference between life and death of a victim in the PHC, and the complications arising from it are largely due to its misuse. Proper instruction regarding the use of the tourniquet is of paramount importance so that the application of this tool is effective and that the possible damages arising from its application are minimal and, if they occur, reversible.